(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
This research was carried in Latakia Governorate ) Al-Hanadi nursery(, as it is considered one of the most important production centers in the agricultural field. The economic study was conducted in an olive seedling production center, which specializes in producing different types of olive seedlings:( Al-Khudairi, Sourani, and Al-Darmali. And diabetes). The research aimed to study the reality of olive seedling production in Al Hanadi Agricultural Nursery during the period (2016-2021), and to study the economic efficiency of olive seedling production in the nursery, using descriptive analysis methods, and relying on nursery data collected during the year 2021, including nursery characteristics and cost calculations. And revenues The results showed that the production of seedlings in the olive nursery increased significantly during the period studied, and that the process of producing seedlings is a profitable process in view of the net profits achieved by the nursery, where the profit percentage reached 30% and the economic efficiency was 1.5. It was also shown that the percentage of recycled seedlings within the nursery increased significantly. Which indicates that marketing the plant is the decisive factor in determining the outcome of the production process. This requires reconsidering the plan for producing seedlings in quantity and quality in the olive nursery, and reducing the quantities of seedlings produced, so that the nursery can increase its profits to a greater extent than it is at the present time.